Inovasi Variasi PÃoduk Bakpia Sekâ€™Eco, Pelatihan Sistem Manajemen Keuangan dan PemasaÃan Upaya Peningkatan Daya Saing - Firdarini, Khoirunnisa Cahya; Kundala, Manendha Maganitri; Novitasari, Dwi; Azzzahra, Dhea; Sugiarti, Kartika (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Bakpia is a typical food of the Special Region of Yogyakarta that has great potential to be developed into a product that is able to compete not only locally but also nationally. This potential needs to be achieved, among others, by creating different flavor variants so that it becomes a unique characteristic and improving financial management and marketing. This community service activity is focused on Bakpia Sek'eco partners by innovating ebi bakpia which has a savory taste that has never existed before, improving financial management capabilities by converting manual financial records to Accurate online software and maximizing the use of social media to expand the marketing network. This community service activity begins with conducting an initial survey, socialization and mentoring and training for Bakpia Sek'eco partners with the aim that partners can increase sustainable competitiveness amidst the tight competition in the bakpia industry, especially in the Special Region of Yogyakarta